The Effect Of Gallery Walk Strategy On Students' Ability In Writing Procedure Text - Rani Safitri; Enni Maisaroh (Universitas Potensi Utama, 2022)
The purposes of researcher was about figuring out if there was an effect in improving the students' ability on writing procedure text by using the Gallery Walk. The research problem was whether there is effect in Gallery Walk on students’ ability in learning writing procedure text. The aim of the research was to find out the effectiveness of the Gallery Walk in the students' writing ability on procedure text. In this research, the researcher used the pre-experimental design method in one group pre-test and post-test design. There were two variables research namely the independent variable (Gallery Walk Strategy) and dependent variable (students' ability in writing procedure text). The researcher collected the data on the written test (pre-test and post-test). Each written test was a type of questions in the multiple choice form. Each test consisted of 30 items. These data would be calculated into the total and mean score. It would be analyzed the validity, reliability, homogenity, normality and T-test by using SPSS. Based on the findings and discussion of the study, the research showed that the use of gallery walk had an effect in students' ability on procedure text. It could be seen by the mean of pre-test which was Mean Score 63,73 and post-test was 85,43. The value of to (t-count) = 0,716 and (t-table) = 0,266. It meant that the value of t-count was higher than t-table. It could be stated that the gallery walk was effective in students' writing ability on procedure text.